Handbooks of macroeconomics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 1999)
The aim of the Handbooks in economics series is to produce handbooks for various branches of economics.Each handbook provides self contained survey of the current state of a branch economics.Handbook of economics is in three volumes.The Vol.I. covers Empi
Keywords: MACROECONOMICS-HANDBOOKS, MANUALS, ETC; FISCAL POLICY-HANDBOOKS, MANUALS, ETC; MONETARY POLICY-HANDBOOKS, MANUALS, ETC; ECONOMIC FLUCTUATIONS-HANDBOOKS, MANUALS, ETC